2018
DOI: 10.1158/1078-0432.ccr-18-0851
|View full text |Cite
|
Sign up to set email alerts
|

Nilotinib as Coadjuvant Treatment with Doxorubicin in Patients with Sarcomas: A Phase I Trial of the Spanish Group for Research on Sarcoma

Abstract: Nilotinib plus doxorubicin showed to be synergistic regarding apoptosis in several sarcoma cell lines. A phase I/II trial was thus designed to explore the feasibility of nilotinib as coadjuvant of doxorubicin by inhibiting MRP-1/P-gp efflux activity. The phase I part of the study is presented here. Nilotinib 400 mg/12 hours was administered in fixed dose from day 1 to 6, and doxorubicin on day 5 of each cycle. Three dose escalation levels for doxorubicin at 60, 65, and 75 mg/m were planned. Cycles were repeate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…In contrast, recent studies have demonstrated that several FDA-approved therapeutic agents such as osimertinib and midostaurin exhibited an inhibitory effect on ABCB1-mediated drug efflux, thus resensitizing ABCB1-overexpressing multidrug-resistant cancer cells to cytotoxic anticancer agents [29,[44][45][46]. Moreover, the advantage of using combination therapy against multidrug-resistant cancers was demonstrated in a recent phase I study of concomitant administration of doxorubicin with nilotinib as a co-adjuvant treatment in sarcoma patients [47]. Similarly, studies have reported that a combination-therapy of lapatinib and capecitabine was superior to capecitabine alone in patients with human epidermal growth factor receptor 2 (HER2)-positive advanced breast cancer [48,49], whereas erlotinib significantly improved the survival of patients with advanced pancreatic cancer receiving gemcitabine [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, recent studies have demonstrated that several FDA-approved therapeutic agents such as osimertinib and midostaurin exhibited an inhibitory effect on ABCB1-mediated drug efflux, thus resensitizing ABCB1-overexpressing multidrug-resistant cancer cells to cytotoxic anticancer agents [29,[44][45][46]. Moreover, the advantage of using combination therapy against multidrug-resistant cancers was demonstrated in a recent phase I study of concomitant administration of doxorubicin with nilotinib as a co-adjuvant treatment in sarcoma patients [47]. Similarly, studies have reported that a combination-therapy of lapatinib and capecitabine was superior to capecitabine alone in patients with human epidermal growth factor receptor 2 (HER2)-positive advanced breast cancer [48,49], whereas erlotinib significantly improved the survival of patients with advanced pancreatic cancer receiving gemcitabine [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Geyer et al and Cetin et al, reported that the efficacy of capecitabine was significantly improved by lapatinib in HER2-positive metastatic breast cancer patients who have previously failed conventional anticancer therapies [63,64]. More recently, encouraging results were reported in a phase I study using nilotinib as co-adjuvant treatment with doxorubicin in patients with sarcomas [65]. Collectively, these studies have shown that, in principle, a combination therapy of a cytotoxic anticancer agent and a molecularly targeted agent with a drug transporter modulating activity is a feasible therapeutic strategy against multidrug-resistant cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Phase I results showed that the combination is feasible and it does not add substantial toxicity in comparison with doxorubicin alone. Of note, it was reported a decreased expression of both MRP-1 and P-gp after 5 days of Nilotinib treatment [85]. The results of the phase II part are expected to be published soon.…”
Section: Abc Efflux Pumpsmentioning
confidence: 92%